Sudden cardiac death in congenital heart disease—a narrative review and update - Han, Frank (Frontiers in Cardiovascular Medicine, 2025)
The spectrum of congenital heart disease is extremely varied, from simple septal defects all the way up to complex heterotaxy with multiple overlapping congenitally malformed regions of the heart. While surgical repair has come a long way since the first congenital cardiac surgery, a B-T-T shunt, an unmet need remains as the population continues to experience sudden cardiac arrest at a greater rate than the general population. Many advances in pacing and cardioversion have occurred to address bradyarrhythmias and tachyarrhythmias, but these carry their own adverse effect profile and limitations. This review aims to survey the field, summarize advances, and provide suggestions for future research directions.